Crystallochemical indexes and geothermobarometric calculations as a multiproxy approach to P-T condition of the low-grade metamorphism: The case of the San Luis Formation, Eastern Sierras Pampeanas of Argentina - Verdecchia, Sebastián Osvaldo (2019)
In this work, crystallochemical indexes and geothermobarometric calculations are used together to estimate the P-T condition in low-grade metamorphic units of the San Luis Formation from Sierra de San Luis (Eastern Sierras Pampeanas of Argentina). Phyllites and slates from this formation record at least two episodes of white mica (Wm) and chlorite (Chl) growth associated with main D1-S1 (Wm2-Chl1) and local D2-S2 (Wm3-Chl2) stages. Mean KICIS values of 0.30 (Western Belt) and 0.23 Δ°2θ (Eastern Belt) were determined for the <2 μm fraction. Moreover, since the average grain size of the Wm2 exceeds 10 μm, KICIS values were also measured for the 10–20 μm fraction ranging between 0.22 and 0.24 Δ°2θ for both belts. For those fractions, the KICIS values indicate epizone conditions, associated with temperatures higher than 300 °C. These values are comparable to temperatures obtained from chlorite thermometers, 316°–416 °C in Western Belt and 261°-403 °C in the Eastern Belt. Pressure values for D1 stage constrained from chlorite – white mica – quartz – H2O equilibrium are 2.5–5.1 kbar in the Western Belt, and at 3.3–4.7 kbar in Eastern Belt. The pressures are consistent with white mica b parameter values measured in samples from Western Belt (9.006 to 9.025 Å) and Eastern Belt (9.003 to 9.020 Å), linked to intermediate thermal gradients (25–35 °C/km). The identification of increasing P-T condition paths in low-grade metasedimentary successions is not easy in the absence of higher grade rocks; in these situations, a systematic sampling and analysis of dozens of samples must be carried out. The very good correlation between crystallochemical index values (Kübler index and white mica b parameter) and thermobarometric calculations (empirical and semi-empirical chlorite thermometers and thermobarometry for chlorite – white mica – quartz – H2O equilibrium) presented in this work argues in favor of the development of a multiproxy study strategy in this type of low-grade metasedimentary successions that involve: (1) a systematic sampling of metapelite levels for X-ray diffraction study (mineralogical and crystallochemical indexes with a rapid implementation allowing a dense systematic sampling); (2) the recognition of variations in the P-T conditions from KI and b parameter values and the consequent selection of metapelitic samples for analyzing mineral chemistry and thermobarometric calculations. In order to facilitate these calculations, a user-friendly spreadsheet for crystallochemical indexes and chlorite thermometry calculations is also provided.